Common core mathematics in a PLC at work - Zimmermann, Gwen; Kanold, Timothy D. (Solution Tree Press, 2012)
Focus your curriculum to heighten student achievement. Learn 10 high-leverage team actions for grades 9-12 mathematics instruction and assessment. Discover the actions your team should take before a unit of instruction begins, as well as the actions and formative assessments that should occur during instruction. Examine how to most effectively reflect on assessment results, and prepare for the next unit of instruction.